PENGARUH INTERNET FINANCIAL REPORTING, TINGKAT PENGUNGKAPAN INFORMASI BERBASIS WEBSITE, DAN JUMLAH SAHAM BEREDAR TERHADAP FREKUENSI PERDAGANGAN SAHAM - Erna Sulistyowati; Meidy Tiara Nur Sausan; Faluthia Fitri Puspaningrum (Behavioral Accounting Journal, 2021)
The objectives of this study are: (1) to prove, test, empirically and analyze the impact of Internet Financial Reporting on Stock Trading Frequency, (2) to prove, test, empirically and analyze the impact of the Website-Based Information Disclosure Level on Stock Trading Frequency, (3) Testing, proving, by empirical means and analyzing the impact of the Number of Outstanding Shares on the Trading Frequency of Shares. This study uses quantitative methods using secondary data taken from the company's website and the IDX through www.idx.co.id in 2016-2018. In this study, we will use data analysis techniques with multiple linear regression with the help of SmartPLS 3.29. The results of this study show that (1) "Internet Financial Reporting" has no effect on Stock Trading Frequency, (2) Website-Based Information Disclosure has no effect on Stock Trading Frequency, (3) Number of Outstanding Shares has no effect on Stock Trading Frequency. The implications of this research are paying attention to financial information in the company that is listed through the website then investors can predict future financial performance and prospects and can make decisions related to investment decision making, by uploading and updating information owned by the company can provide education to the public. users and prosper the company. The high and low level of disclosure of company website information will have a small impact on the impact of disclosure on investor decisions. In addition, taking into account factors other than the number of outstanding shares, such as fundamental factors and stock prices, can attract investors to invest in the company, because basically investors in buying shares must choose liquid shares.